PERANCANGAN APLIKASI PENGGAJIAN KARYAWAN BERBASIS ANDROID DAN DART FLUTTER PADA PT ANDALAN K3 MENGGUNAKAN MODEL WATERFALL - Wiguna, Nafis Surya; Nanang, Nanang (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
In the era of digital transformation, the use of mobile technology, especially Android, has become common and has had a significant impact on various aspects of life, including the business world. By involving many employees who use Android devices as their primary tool, the opportunity to increase affordability and convenience through Android-based payroll applications is enormous. The Waterfall method was chosen as a systematic approach in designing this application. The steps from system requirements, analysis, design, coding, testing/verification, to maintenance are carried out sequentially and structured. This study entitled